ANALISIS KESULITAN GURU DALAM MENGEMBANGKAN RPP TEMATIK - Marlinda Mulu; Quintus Van Mujus; Hironimus Wejang (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
The problem that lies behind the research this is the teachers experiencing difficulties in developing the RPP Thematic. The aim of this research is to find out the difficulties of teachers in developing lesson plans Thematic and factors cause difficulty that experienced teachers in developing lesson plans Thematic. The method of writing a thesis is, that the method of study literature. Methods of literature is the method that is used by reviewing books or journals without requiring the research field. Mechanical collection of data in the writing of the thesis is, that is done by way of searching journals and book -book. Based on the results of the study found that difficulties were experienced by teachers in developing lesson plans thematic due to not follow the training curriculum in 2013, is difficult to define indicators and objectives of learning and difficult to determine ratings. In addition to the factors causing difficulty teachers in developing lesson plans thematic is as follows: facilities and infrastructure are less adequate, provision of material teaching the less, as well as teachers difficult making RPP curriculum in 2013 in the study. Based on the results of the study, can be concluded that by following the training curriculum in 2013 to overcome the difficulties of teachers in developing lesson plans Thematic well as providing the means and infrastructure are adequate and provide materials teaching in accordance with the number of students is how to address the factors causing difficulties teachers in developing lesson plans Thematic.